Vegetable oil based-polymers reinforced with wood flour - Mosiewicki, Mirna Alejandra (2008)
Liquid polymer precursors were synthesized from vegetable oils to be utilized in the preparation of oil based-resins to be later reinforced with a filler also obtained from natural sources. In this work, an unsaturated oil, tung oil, produced in the region was selected as raw material. The vegetable oil was chemically functionalized to obtain a polyol to be further used in polyurethane formulations. Different analysis techniques were used to investigate the hydroxyl content in the modified oil. Oil based composites containing pine wood flour as filler were prepared and mechanically tested.